Agro-Economic Impact of Climate Resilient Practices on Farmers in Anantapur District of Andhra Pradesh - Harikrishna, Yeragorla Venkata; Naberia, Seema; Pradhan, Sabyasachi; Hansdah, Paraw (Indian Journal of Extension Education, 2020)
Climate change is one of the serious challenges to the agriculture sector in order to ensure nutritional and food security for growing population. National Innovations on Climate  Resilient Agriculture (NICRA) project aims to improve resilience of Indian agriculture to climate change and climate vulnerability. The present study was conducted to know the impact of the climate resilient technologies upon the NICRA beneficiaries in Anantapur district of Andhra Pradesh. The study was conducted with a sample of 60 respondents from three NICRA project implementing villages. Before-after comparison of NICRA beneficiaries was employed to identify the project impact and the difference was tested using paired t-test and found that it was statistically significant. The results of the study reveals that area under irrigation, crop yield, cropping intensity and annual income of NICRA beneficiaries after the project interventions was significantly higher than that of before the implementation of the interventions. More than fifty percent respondents had medium level of impact of the climate resilient technologies. This study helps the implementing institutions in redesigning the interventions for wide adaption of climate resilient practices.